Influences of cryogenically treated work material on near-dry wire-cut electrical discharge machining process. (1st March 2022) - Kannan, Elango; Trabelsi, Youssef; Boopathi, Sampath; Alagesan, Sivapragasam
Abstract: In this research, influences of cryogenically treated Inconel 718 work material in near-dry wire-cut electrical discharge machining (WEDM) characteristics have been studied using argon-mist (mixing of pressurized argon gas and minimum amount of tap-water) and a reusable Molybdenum wire tool. The effect of cutting parameters (pulse width (PW), spark current(C), pulse interval (PI), and flow rate(F)) on surface roughness (SR) and cutting rate (CR) and using Box-Behnken response surface analysis. It was observed that CR and SR are increased by increasing PW, and C; conversely, reduced by increasing PI. The technique for order of preference by similarity to ideal solution (TOPSIS) method has been utilized to estimate the best parameters' settings for improving both machining characteristics. The optimum CR (9.81 mm 3 min) −1 and SR (1.9 μ m) have been obtained by optimum settings of 4 Ampere spark current, PW of 20 μ s, PI of 72 μ s, and 18 ml min −1 of the flow rate of mixing water using the TOPSIS method. The best settings of cutting parameters obtained from the TOPSIS method were considered to compare the near-dry WEDM performance using cryogenically treated/untreated work materials. It was observed that CR and SR of the cryogenically treated work material are 9.17% increased and 21.58% reduced than the untreated work material due to an increase in electrical and thermal conductivities.